Perubahan Lingkungan Fisik Tanah Sawah Dengan Penambahan Bahan Organik Pada Berbagai Cara Pemberian Air - Harsono Harsono (agriTECH, 1998)
The problem faced by the flooded rice field are the deficiency of nitrogen, phosphorus and potassium, the toxic of Fe, Mn, Al, and Bo to plant. When the puddled soil are dried the structure of soil becomes massive. Hard consistency caused the roots of crop do not able to penetrate the soil. To overcome those problems, the research of the addition' of organic matter into the soil under various method of irrigation was conducted. The experimental design strip split plot design was used. The treatments were the method of irrigatiOn as horizontal factor (a), duration of organic matter incorporated into the soil as vertical factor (b). The kind of organic matter as subplot factors (c). The crops to be tested were rice (IR - 36) and soybean. The field experiment was carried out in KP4 UGM experiment station, Berbah, Sleman Yogyakarta. The results of this experiment indicated that the bulk density increased with time from the plowing up to the harvest. However, the hydraulic conductivity of soil decreased. The lowest bulk density was in the plots buried by straw (0.85 gr/cm3) and the highest was buried by the leaf of gliriside (Glericidia sepium) (0.96gr/c). The addition of organic matter into the soil increased nitrogen, phosphorous and potassium. The residue effects of those treatments on soil grown by the soybean indicated that the soil aggregate of 2 mm increased by 40% in the plots buried by the straw. The highest yield of rice was on the plots buried by leaf of gliriside under the intermittent irrigation with the yield as higher as 6.53 ton/ha.